Sense of Purpose and Progress Towards Degree in Freshman College Students. (May 2023) - Yukhymenko-Lescroart, Mariya A.; Sharma, Gitima
This study examined whether first-time full-time freshman students' sense of purpose predicted their progress towards a degree. Freshman students ( N  = 421, 62.2% females) completed self-report measures of sense of purpose and academic commitments within the first month of starting college; a year later, the data on first-year progress towards a degree were matched with their responses. Structural equation modeling showed that while a sense of purpose did not directly predict progress towards a degree, awakening to purpose and altruistic purpose both had indirect positive effects on first-year GPA, academic standing, and retention through degree commitment. Additionally, altruistic purpose had indirect positive effects on first-year GPA through academic identity. The findings highlight that a sense of purpose may play an important role in persistence and attainment of a degree among college students.